Hydration practices of runners during training vs competition - Ferreira, F. G.; Gonçalves Pereira, L.; Rodrigues Xavier, W. D.; Muniz Guttierres, A. P.; Campos Santana, A. M.; Brunoro Costa, N. M.; Bouzas Marins, J. C. (Archivos de medicina del deporte, 2016)
Background: Appropriate hydration ensures that the athlete is in ideal condition during exercise. Inadequate hydration practices are still present among athletes participating in different types of sports. This could be the result of a low level of knowledge concerning the importance of hydration for athletic performance. The purpose of this study was to evaluate the level of knowledge and the hydration practices of the runners in training and competition.Method: This study used an exploratory method involving a questionnaire containing 19 objective questions related to hydration habits and level of knowledge about hydration, as reported in prior studies, which included questions categorized into three parts: demographic characteristics, hydration habits during competition and training, and hydration knowledge. A total of 412 athletes (36.1 ± 12.9 years old) with a high experience in the sport (11.2 ± 10.9 years) were evaluated.Results: A significant difference (p = 0.0012) was observed for reported hydration practices between training and competi-tions. Moreover, the data revealed that a large number of runners (41 % in competitions and 54.4% in training) had inadequate hydration habits because they did not always consume fluids. Increased consumption of fluids in the competitions was also observed. Only 35.4% of athletes consumed sports drinks, while 3.88 % had never consumed fluids during training, and 1.5% never consumed fluids in competition. Few athletes (23.2%) weighed themselves before and after exercising. Participants answered 66.6% of hydration knowledge questions correctly.Conclusion: Runners were not able to transfer their knowledge about proper hydration during both training and competition practices.